2018
DOI: 10.1177/1729881418783158
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dynamics and speech on understanding humanoid facial expressions

Abstract: Human communication relies mostly on nonverbal signals expressed through body language. Facial expressions, in particular, convey emotional information that allows people involved in social interactions to mutually judge the emotional states and to adjust its behavior appropriately. First studies aimed at investigating the recognition of facial expressions were based on static stimuli. However, facial expressions are rarely static, especially in everyday social interactions. Therefore, it has been hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 76 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…Ghazali et al [60] found that facial expressions resulted in higher social agency scores compared to voice alone. Lazzeri et al [98] found that, regardless of virtual avatar or robot, "muted" facial expressions without vocalizations were confusing. Read and Belpaeme [150] found that nonverbal utterances conveyed classifiable emotion.…”
Section: Accent and Dialectmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghazali et al [60] found that facial expressions resulted in higher social agency scores compared to voice alone. Lazzeri et al [98] found that, regardless of virtual avatar or robot, "muted" facial expressions without vocalizations were confusing. Read and Belpaeme [150] found that nonverbal utterances conveyed classifiable emotion.…”
Section: Accent and Dialectmentioning
confidence: 99%
“…Findings show that people can perceive emotion through voice, if certain conditions are met. The inclusion of voice affect to visual expressions of affect appears key (e.g., References [74,98]), with some work suggesting that voice alone is more difficult to interpret (e.g., Reference [33]). For instance, if there is a mismatch between bodily affective cues and vocal affect, then people are confused (e.g., Reference [183]).…”
Section: Empiricalmentioning
confidence: 99%
“…Research on robots concerns both the anthropomorphic features of robots and the expression of realistic behavior by robots. Lazzeri et al concentrated on the research of facial expressions performed by robot Eva because facial expressions convey emotional information that allows people to get involved in social interactions [44].…”
Section: Humanoid Robotmentioning
confidence: 99%
“…Moreover, in the previous studies, the authors explained how age-friendly robots were successfully used for various applications, such as companioning, assisting, playing, and overcoming users’ inabilities [ 26 ]. The research has also indicated that interactions between robots and the elderly could be improved for better outcomes [ 41 ]. Especially people’s acceptance of robots, motivation to use electronic devices and enjoyment in daily routines [ 3 , 20 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%